Marcadores Discursivos e(m) Tradução II - Ana Paula Loureiro (Investigação, 2019)
This volume includes some of the contributions from renowned experts to the 3rd and 4th International Colloquium MarDisT held at the Faculty of Arts and Humanities, University of Coimbra in 2017 and 2018. The contributions address different languages, theoretical perspectives, genres of text, translation problems, and difficulties in SLA. Discourse markers are however the common denominator. The wide range of issues covered will certainly inspire further research projects.